2013
DOI: 10.1007/s10198-012-0455-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health on labour supply in nine former Soviet Union countries

Abstract: This paper examines for the first time the consequences of ill health on labour supply for a sample of nine countries from the former Soviet Union (FSU), using a unique multicountry household survey specifically designed for this region. We control for a wide range of individual, household, and community factors, using both standard regression techniques and instrumental variable estimation to address potential endogeneity. Specifically, we find in our baseline ordinary least squares specification that poor he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Thus, using RLMS survey data collected in 1997–2004, Abegunde et al [9] found a significant positive association between a combined dummy for non-chronic diseases and the probability of missing days of work for heads of households. A study using data collected in ten post-Soviet countries [24], including Russia, found that poor health was associated with a 15 % lower probability of work in the community fixed-effects specification, which is comparable to the result we found in the OLS model (i.e., about 14 % lower probability of work). Finally, Suhrcke et al [4] found that in Russia, self-assessed good health was mostly unrelated to log of hours worked per week.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, using RLMS survey data collected in 1997–2004, Abegunde et al [9] found a significant positive association between a combined dummy for non-chronic diseases and the probability of missing days of work for heads of households. A study using data collected in ten post-Soviet countries [24], including Russia, found that poor health was associated with a 15 % lower probability of work in the community fixed-effects specification, which is comparable to the result we found in the OLS model (i.e., about 14 % lower probability of work). Finally, Suhrcke et al [4] found that in Russia, self-assessed good health was mostly unrelated to log of hours worked per week.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, the magnitude of the difference is quite unexpected for most age groups. One potential reason for this is that women may feel more responsible for their families and thus continue working despite being in poor health [22–24]. …”
Section: Discussionmentioning
confidence: 99%
“…The responses ranged from zero (poor) to three (very good). From this we created a binary variable "good heath", with individuals reporting "good" or "very good" health being accorded a "1″, and those reporting "poor" or "fair health" a "0″, as done in other studies [34].…”
Section: Dependent Variablementioning
confidence: 99%
“…Following Goryakin et al (2014) as an alternative analysis, we create the 'good health' variable that takes value '1' if individuals reported 'good' or 'very good' health, and value '0' when individuals report 'poor' and 'fair' health, and we include this dummy variable in Eqs. (1) to (5) as a measure of self-reported health.…”
mentioning
confidence: 99%